Impaired telomere integrity and rRNA biogenesis in PARN‐deficient patients and knock‐out models - Maname Benyelles; Harikleia Episkopou; Marie‐Françoise O'Donohue; Laëtitia Kermasson; Pierre Frange; Florian Poulain; Fatma Burcu Belen; Meltem Polat; Christine Bole‐Feysot; Francina Langa‐Vives; Pierre‐Emmanuel Gleizes; Jean‐Pierre de Villartay; et al. (EMBO Molecular Medicine)
Abstract PARN, poly(A)‐specific ribonuclease, regulates the turnover of mRNAs and the maturation and stabilization of the hTR RNA component of telomerase. Biallelic PARN mutations were associated with Høyeraal–Hreidarsson (HH) syndrome, a rare telomere biology disorder that, because of its severity, is likely not exclusively due to hTR down‐regulation. Whether PARN deficiency was affecting the expression of telomere‐related genes was still unclear. Using cells from two unrelated HH individuals carrying novel PARN mutations and a human PARN knock‐out (KO) cell line with inducible PARN complementation, we found that PARN deficiency affects both telomere length and stability and down‐regulates the expression of TRF1, TRF2, TPP1, RAP1, and POT1 shelterin transcripts. Down‐regulation of dyskerin‐encoding DKC1 mRNA was also observed and found to result from p53 activation in PARN‐deficient cells. We further showed that PARN deficiency compromises ribosomal RNA biogenesis in patients' fibroblasts and cells from heterozygous Parn KO mice. Homozygous Parn KO however resulted in early embryonic lethality that was not overcome by p53 KO. Our results refine our knowledge on the pleiotropic cellular consequences of PARN deficiency.